Classroom Management in the Digital Era by Utilizing Learning Technology in Elementary Schools - Rachma Nurfitria; Sofyan Iskandar; Primanita Sholihah Rosmana; Eldyana Citra Laksita; Wilda Nur Laila (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to examine managing classes in the digital era by utilizing technology for learning in elementary schools and its impact on quality and providing benefits to students. Classroom management learning is In the current digital era, in managing classes in elementary schools, there are many meaningful transitions that take place by utilizing them in the learning process. Technology recommends various tools and resources that can increase the need and accuracy of learning methods, both for teachers and students. This article explores how technology can be used to manage classes more efficiently, overcome emerging challenges, and maximize the potential of education in elementary schools. Some important aspects explained include using software in the form of online learning platforms and digital collaboration tools. In addition, this article also highlights the importance of developing digital skills for teachers and students, as well as highlighting the important role of technology in creating inclusive and interactive learning environments. By utilizing technology optimally, we hope to create a learning atmosphere that is more enjoyable, adaptive, and in line with students' needs in this digital era.Classroom management is an approach that combines various disciplines to deliver a more holistic and relevant classroom management learning experience for students. This literature study analyzes various previous studies that discuss effectiveness in managing classes, in the context of primary and secondary education up to higher education. The results of the literature review show that classroom management learning can improve the quality of digital learning through presenting material that is more contextual and interactive. This method was also found to be effective in improving classroom management, due to active participation and the connection between lesson material and real life.